Mechanisms underlying the effects of prenatal psychosocial stress on child outcomes: beyond the HPA axis - Beijers, Roseriet; Buitelaar, Jan K.; de Weerth, Carolina (European child & adolescent psychiatry, 2014)
Accumulating evidence from preclinical and clinical studies indicates that maternal psychosocial stress and anxiety during pregnancy adversely affect child outcomes. However, knowledge on the possible mechanisms underlying these relations is limited. In the present paper, we review the most often proposed mechanism, namely that involving the HPA axis and cortisol, as well as other less well-studied but possibly relevant and complementary mechanisms. We present evidence for a role of the following mechanisms: compromised placental functioning, including the 11β-HSD2 enzyme, increased catecholamines, compromised maternal immune system and intestinal microbiota, and altered health behaviors including eating, sleep, and exercise. The roles of (epi)genetics, the postnatal environment and the fetus are also discussed. We conclude that maternal prenatal psychosocial stress is a complex phenomenon that affects maternal emotions, behavior and physiology in many ways, and may influence the physiology and functioning of the fetus through a network of different pathways. The review concludes with recommendations for future research that helps our understanding of the mechanisms by which maternal prenatal stress exerts its effect on the fetus.